Framing Espos.id dan Kompas.com dalam Pemberitaan Pemilihan Calon Gubernur Jawa Tengah Tahun 2024 - Candra Permana; Syafawi Ahmad Qadzafi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This article aims to analyze the news framing of the gubernatorial and vice-gubernatorial candidate pair for Central Java, Ahmad Luthfi–Taj Yasin, in the 2024 gubernatorial election as reported by Espos.id and Kompas.com. Using a framing analysis approach based on Robert N. Entman's model, the study finds that Espos.id tends to highlight the Ahmad Luthfi–Taj Yasin pair more prominently through more intensive coverage, the use of positive diction such as “ready to win” and “the right figure to lead Central Java,” and narratives involving national figures as a form of legitimacy. Espos.id's framing presents the pair as a symbol of the continuity of national power and regional stability. In contrast, Kompas.com presents more neutral reporting by proportionally covering both candidate pairs, emphasizing issues of state official neutrality, electability dynamics, and maintaining a focus on democratic principles and political ethics.Thus, the study concludes that Espos.id tends to construct a framing that favors Ahmad Luthfi–Taj Yasin, while Kompas.com maintains balanced information in line with the principles of objective journalism.